Safety of Intravenous Methamphetamine Administration During Ibudilast Treatment. Issue 4 (August 2016) - DeYoung, Dustin Z.; Heinzerling, Keith G.; Swanson, Aimee-Noelle; Tsuang, John; Furst, Benjamin A.; Yi, Yi; Wu, Ying Nian; Moody, David E.; Andrenyak, David M.; Shoptaw, Steven J.
Abstract : Background: Methamphetamine dependence is a significant public health concern without any approved medications for treatment. We evaluated ibudilast, a nonselective phosphodiesterase inhibitor, to assess the safety and tolerability during intravenous methamphetamine administration. We conducted a randomized, double-blind, placebo-controlled, within-subjects crossover clinical trial. Methods: Participants received ibudilast (20 mg twice daily followed by 50 mg twice daily) and placebo, with order determined by randomization, and then underwent intravenous methamphetamine challenges (15 and 30 mg). We monitored cardiovascular effects, methamphetamine pharmacokinetics, and reported adverse events. Results: Ibudilast treatment had similar rates of adverse events compared with placebo, and there was no significant augmentation of cardiovascular effects of methamphetamine. Pharmacokinetic analysis revealed no clinically significant change in maximum concentration or half-life of methamphetamine with ibudilast. Conclusions: Methamphetamine administration during ibudilast treatment was well tolerated without additive cardiovascular effects or serious adverse events, providing initial safety data to pursue ibudilast's effectiveness for the treatment of methamphetamine dependence. Abstract : Supplemental digital content is available in the text.